2021
DOI: 10.3390/v13112203
|View full text |Cite
|
Sign up to set email alerts
|

Use of Slaughterhouses as Sentinel Points for Genomic Surveillance of Foot-and-Mouth Disease Virus in Southern Vietnam

Abstract: The genetic diversity of foot-and-mouth disease virus (FMDV) poses a challenge to the successful control of the disease, and it is important to identify the emergence of different strains in endemic settings. The objective of this study was to evaluate the sampling of clinically healthy livestock at slaughterhouses as a strategy for genomic FMDV surveillance. Serum samples (n = 11,875) and oropharyngeal fluid (OPF) samples (n = 5045) were collected from clinically healthy cattle and buffalo on farms in eight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…This could have impacted our model, for example, by flattening the impact of the temporal effects in other years with the result of identifying similar predicted risk through time. Despite these limitations, this study provides compatible results with other studies [ 8 , 13 , 15 , 18 , 25 ] regarding animal and FMDV movement in Vietnam.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This could have impacted our model, for example, by flattening the impact of the temporal effects in other years with the result of identifying similar predicted risk through time. Despite these limitations, this study provides compatible results with other studies [ 8 , 13 , 15 , 18 , 25 ] regarding animal and FMDV movement in Vietnam.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we utilized two types of data available from Vietnam: (a) data on the reported number of FMD cases per province per year (Department of Animal Health, Vietnam), and (b) FMDV VP1 sequences generated from various research and surveillance projects conducted in Vietnam [ 8 , 9 , 15 , 22 , 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FMD is endemic in several countries in Asia. The main serotypes of FMDV circulating in this region are O, A, and Asia 1 [ 12 , 13 ]. Numerous countries in Southeast Asia, including Cambodia, Lao PDR, Malaysia, Myanmar, Thailand, and Vietnam, are endemic to FMD [ 9 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main serotypes of FMDV circulating in this region are O, A, and Asia 1 [ 12 , 13 ]. Numerous countries in Southeast Asia, including Cambodia, Lao PDR, Malaysia, Myanmar, Thailand, and Vietnam, are endemic to FMD [ 9 , 13 , 14 ]. Between 2007 and 2017, a total of 4961 FMD outbreaks were reported in these countries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%